KAJIAN TINGKAT PENDAPATAN NELAYAN DENGAN STATUS SUMBERDAYA IKAN DI SUNGAI WOYLA KABUPATEN ACEH BARAT - Zuriat Zuriat; Yuliani Yuliani (Journal of Aceh Aquatic Sciences, 2017)
Woyla river is one of the fish resources potency in the Woyla district West of Aceh Regency. The research method by using survey method that conducted in April to July 2017. The data processing by using analysis including tabulation and bussiness analysis. The correlation of income level related with with existing of fish resources. Which spesies and amount of spesies that economical valued have important role to give income level in consist of freshwater catfish, snakehead fish and etc. The result of biodiversity that gaining from various fishes that contributed to income level. The fishing result showed that the Station 2 much more than other station namely snakehead fish that give income bigger. According to observed that the fishes that succeed to catch at Woyla river as much as 197 fishes in consist of 13 spesies that represented 10 famili. Species diversity at Woyla River is relatively low (H’<1) with diversity index (H’) on average 0,0473 (low) that showed fish resources status is needed to elevated. Average income per month is Rp.2.472.190.- with B/C ratio more than 1. The fishing result on average 5 kg/days or 150 kg/month that purchase value reached 3 million rupiahs by using trap fishing gear.